Serum-Based KRASG12/G13 Mutation Detection Using Droplet Digital PCR: Clinical Implications and Limitations in Colorectal Adenocarcinoma With Tumor Heterogeneity - Kim, Ju Seok; Bae, Go Eun; Kim, Seok-Hwan; Choi, Min Kyung; Yeo, Min-Kyung (Frontiers in Oncology, 2021)
Background: Cell-free DNA (cfDNA) has arisen as an alternative target for evaluating somatic mutations in cancer. KRAS mutation status is critical for targeted therapy in colorectal adenocarcinoma (CRAC). We evaluated KRASG12/G13 mutations in cfDNA extracted from serum and compared the results with KRASG12/G13 mutations detected in tissue samples. We assessed the clinical significance of KRASG12/G13 mutation in serum in regard to recurrence and metastasis of CRAC. Methods: A total of 146 CRAC patients were enrolled, and KRASG12/G13 mutations were evaluated in 146 pairs of serum and tissue samples. In addition, 35 pairs of primary and metastatic CRAC tissue samples were evaluated for KRASG12/G13 mutational status. Results: Detection of KRASG12/13 mutation from serum and tissue had a 55% concordance rate, and serum detection had a sensitivity of 39.8%. Detection of the KRASG12/13 mutation yielded a 14% discordance rate between primary and metastatic tissue. CRAC patients with mutant KRASG12/13 mutation in serum but wild-type KRASG12/13 in tissue had concurrent KRASG12/13-mutant metastatic tumors, indicating spatial genetic heterogeneity. Changes in serum KRASG12/G13 mutation status during postoperative follow-up were associated with recurrence. Conclusion: Although serum detection of the KRASG12/13 mutation cannot substitute for detection in tissue, serum testing can support the interpretation of a CRAC patient’s status in regard to concurrent metastasis. Dynamic changes in serum KRASG12/13 mutation status during follow-up indicated that cfDNA from serum represents a potential source for monitoring recurrence in CRAC patients.